2019
DOI: 10.1152/jn.00667.2018
|View full text |Cite
|
Sign up to set email alerts
|

Automated home cage training of mice in a hold-still center-out reach task

Abstract: An obstacle to understanding neural mechanisms of movement is the complex, distributed nature of the mammalian motor system. Here we present a novel behavioral paradigm for high-throughput dissection of neural circuits underlying mouse forelimb control. Custom touch-sensing joysticks were used to quantify mouse forelimb trajectories with micron-millisecond spatiotemporal resolution. Joysticks were integrated into computer-controlled, rack-mountable home cages, enabling batches of mice to be trained in parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…Within the context of motor control, our findings also encourage to study the role of areas found to be active during movement (such as the visual areas) commonly disregarded in the association to forelimb movement, at the cellular-level (Galiñanes et al, 2018, Karandell and Huber, 2017, Ebina et al, 2018). In the future, it would also be relevant to assess the neocortical dynamics during RtG in a freely moving condition or during performance refinement, considering that cortical areas undergo functional reorganization during learning (Makino et al, 2017; Whishaw et al, 2017; Bollu et al, 2019; Hwang et al, 2019). In sum, our investigation identified a global network of neocortical area associated to successful RtG execution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of motor control, our findings also encourage to study the role of areas found to be active during movement (such as the visual areas) commonly disregarded in the association to forelimb movement, at the cellular-level (Galiñanes et al, 2018, Karandell and Huber, 2017, Ebina et al, 2018). In the future, it would also be relevant to assess the neocortical dynamics during RtG in a freely moving condition or during performance refinement, considering that cortical areas undergo functional reorganization during learning (Makino et al, 2017; Whishaw et al, 2017; Bollu et al, 2019; Hwang et al, 2019). In sum, our investigation identified a global network of neocortical area associated to successful RtG execution.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of motor control, our findings also encourage to study the role of areas found to be active during movement (such as the visual areas) commonly disregarded in the association to forelimb movement, at the cellular-level (Galianes et al, 2018, Karandell and Huber, 2017, Ebina et al, 2018). In the future, it would also be relevant to assess the neocortical dynamics during RtG in a freely moving condition or during performance refinement (Makino et al, 2017; Whishaw et al, 2017; Bollu et al, 2019). In sum, our investigation identified a global network of neocortical areas beyond those previously known to be associated with goal-directed arm movements and suggest that the operating mode of the mouse neocortex underlying unilateral goal-directed movements involves distant communication across bothhemispheres, while encoding of movement parameters occurs locally, and, in the context of our investigations, mostly in the secondary motor areas.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps of most use, the described tool setup be used in automated training, thus enabling high-throughput research methods, a critical avenue for the future of neuroscience. While one may glean how to build joystick rigs from other sources (Bollu et al, 2019), we provide the first documentation of a selfcentering joystick with extensive online task code and offline analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With one coil removed, it takes only 0.18 N to displace the joystick 1 cm. Other solutions include using a near zero resistance joystick designed for rodents, particularly that described in Bollu et al (2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation